0084 Overwork and its impact on workers' health: a cross-country comparison of overwork-related cardiovascular mortalities and its reflection in the taiwanese situation. (21st August 2017) - Lin, Cheng-Kuan; Lin, Ro-Ting
Abstract : Many Asian countries experienced the rapid change in industrial structure, which has resulted in a notable increase in occupational diseases, particularly overwork-related cardiovascular diseases (CVDs). "Overwork" or "Karoshi" has since been a major health concern for workers in Asia. Taiwan is the third country in the world after Japan and Korea where national governments announced criteria to recognise overwork-related CVDs. However, the public's worries persisted, as the criteria seemed unable to solve the problem of long working hours in these countries. In the December 2016 and early 2017, a series of regulatory changes in Taiwan has received significant attentions, triggered by increasing social criticism indicating that Taiwanese regulations lagged behind international labour standards and many highly industrialised countries. As a result, increases in research addressing overwork-related CVDs issues and in the reported CVD cases could be a good reflection of the national policy change. We first compared the trends of research focus in Taiwan with those in Japan and Korea, respectively. We further collected 10 year data for Taiwan and Japan to investigate the impact of introducing a new policy. We found consistent and plausible correlations between the implementation of new policy and the number of recognised overwork-related CVDs. On the other hand, our results of Taiwan suggested a systematic problem of under-recognition of occupational diseases. Although the industrial development contributed to the country's economic growth substantially, the country will need to keep bearing the underlying burden of overwork-related CVDs.